Ross W. Silcock letter to Nicholas S. Halmi regarding bird sightings, February 12, 1978 - Silcock, W. Rosset al (1978)
Letter from Ross W. Silcock to Nicholas S. Halmi regarding bird sightings, February 12, 1978. This item was used as supporting documentation for the Iowa Ornithologists Union Quarterly field report of winter, 1977-1978. Epson - sheet feed/flatbed